2018
DOI: 10.1111/jph.12726
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of fungal latent pathogens and true endophytes associated with fruit trees in Uruguay

Abstract: We have explored the fungal diversity in asymptomatic twigs of apple, peach, pear and blueberry trees, with the objective of discerning between true endophytes and latent pathogens. Several fungal genera containing known bark pathogens were found. Seven Diaporthe species—D. oxe, D. infecunda, D. serafiniae, D. phaseolorum, D. terebinthifolii, D. foeniculina and D. brasiliensis—were identified, along with Botryosphaeria dothidea, Neofusicoccum parvum, Neofusicoccum australe, Cytospora sp., Cytospora acaciae and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 35 publications
(44 reference statements)
2
24
1
Order By: Relevance
“…Fungal lifestyles could change in response to host internal signals or environmental factors (Rai and Agarkar, 2014). As expected, some fungal endophytes isolated in L. radiata have been reported as latent pathogens in other plants, such as members in the genera Fusarium, Phyllosticta, Colletotrichum, Phoma and Diaporthe (Biggs, 1995;Rodriguez and Redman, 2008;Wikee et al, 2013;Demers et al, 2015;Sessa et al, 2018). We assumed that these latent pathogens could exhibit an endophytic lifestyle in L. radiata, because of the existence of alkaloids having antimicrobial activity in planta (Liu and Reinscheid, 2004;Bednarek, 2012;Pusztahelyi et al, 2015).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Fungal lifestyles could change in response to host internal signals or environmental factors (Rai and Agarkar, 2014). As expected, some fungal endophytes isolated in L. radiata have been reported as latent pathogens in other plants, such as members in the genera Fusarium, Phyllosticta, Colletotrichum, Phoma and Diaporthe (Biggs, 1995;Rodriguez and Redman, 2008;Wikee et al, 2013;Demers et al, 2015;Sessa et al, 2018). We assumed that these latent pathogens could exhibit an endophytic lifestyle in L. radiata, because of the existence of alkaloids having antimicrobial activity in planta (Liu and Reinscheid, 2004;Bednarek, 2012;Pusztahelyi et al, 2015).…”
Section: Discussionmentioning
confidence: 76%
“…As expected, some fungal endophytes isolated in L . radiata have been reported as latent pathogens in other plants, such as members in the genera Fusarium , Phyllosticta , Colletotrichum , Phoma and Diaporthe (Biggs, ; Rodriguez and Redman, ; Wikee et al ., ; Demers et al ., ; Sessa et al ., ). We assumed that these latent pathogens could exhibit an endophytic lifestyle in L .…”
Section: Discussionmentioning
confidence: 97%
“…These symptoms have been associated with an assemblage of species comprising D. ambigua, D. amygdali, D. australafricana, D. baccae, D. crousii, D. eres, D. foeniculina, D. oxe, D. passiflorae, D. phillipsii, D. rossmaniae, D. rudis, and D. vaccinii (syn. D. eres) [2,8,17,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Both genera have been extensively associated with the endophytic community in different plants [ 62 , 104 , 105 ] but are also important pathogens of a wide range of hosts such as pepper, soy, alfalfa and many other cultivable plants [ 101 , 106 , 107 ]. Several studies have shown that pathogenic or parasitic fungi are found as endophytes [ 108 , 109 , 110 , 111 , 112 ]. In this situation, endophytes are latent pathogens that infect the plant, and persist in a dormant phase without causing symptoms in the host [ 113 ].…”
Section: Resultsmentioning
confidence: 99%